THE STRATEGIC ROLE OF PUBLIC RELATIONS OF THE REGIONAL OFFICE OF THE MINISTRY OF RELIGIOUS AFFAIRS OF NORTH SUMATRA IN DISSEMINATING ISLAMIC INFORMATION THROUGH ONLINE MEDIA - Nur Hanifah; Muhammad Al Fazar; Fadhlan Rizky Firdaus H. R.; Rizky Adi Candra Nasution; Muhammad Panususnan Harahap (Communicative : Jurnal Komunikasi dan Penyiaran Islam, 2025)
The development of information and communication technology has transformed patterns of interaction and ways of obtaining information, requiring government institutions to undergo digital transformation. This study aims to describe the communication strategy of the Public Relations Division of the Regional Office of the Ministry of Religious Affairs of North Sumatra Province in disseminating public information through online media. Using a qualitative descriptive approach, data were collected through observation and documentation of digital platforms managed by the office, such as the official website, Instagram, and Facebook. The findings reveal proactive, reactive, and collaborative communication strategies implemented across various digital platforms, including the development of the Pusaka application as a center for religious services. The use of online media has enhanced transparency, public participation, and institutional image. However, challenges such as low digital literacy among the public and the spread of hoaxes remain significant obstacles. Therefore, the Public Relations Division has developed educational content, strengthened collaboration with media outlets, and implemented digital literacy programs. These findings underscore the importance of professionalism and adaptability of government public relations in the digital communication era.